Kajian Stilistika Puisi ”Kepada Hawa” Karya Aan Mansyur dan Pemanfaatannya sebagai Materi Ajar Bahasa Indonesia - Amelia, Yuniar Sandy; Hermawan, Muhammad Alfian (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This study aims to examine the poem Kepada Hawa by Aan Mansyur through a stylistic approach to uncover the meaning and aesthetic quality of the language used by the poet. This research employs a descriptive qualitative method with data collection techniques including reading, note-taking, and identification. The analysis reveals that Aan Mansyur consistently utilizes stylistic elements such as diction, sound patterns (rhyme), syntactic manipulation, and figurative language (simile, metaphor, and hyperbole). Specific rhyme patterns help create mood and tone, while syntactic structure and stylistic choices enhance the emotional expression of the poem. Symbolic imagery such as “red apple” and “faithful snake” enrich the portrayal of love, sacrifice, and sincerity conveyed by the poet. This study demonstrates that a stylistic approach is effective in uncovering implicit meanings and highlighting the aesthetic beauty in modern poetry. In addition, this study can be a learning resource for student in school in exploring the elements in poetry.